Odpowiedź :
ad.1
P=a×h
a=P/h
ad.2
a). P=10π≈31,4
b). P=0,4π≈1,256
ad.3
a). 8-0,9=7,1
b). m=k-z
k=m+z
z=k-m
c). k=m+z
ad.4
m=F/a
a=F/m
P=a×h
a=P/h
ad.2
a). P=10π≈31,4
b). P=0,4π≈1,256
ad.3
a). 8-0,9=7,1
b). m=k-z
k=m+z
z=k-m
c). k=m+z
ad.4
m=F/a
a=F/m
1. P=a * h / :h
a= P/h
2.a) L= 10π ( cm)
b) d= 2*r
d= 2*0,2
d=0,4 (dm)
L= 0,4π (dm)
3.k - z=m
m= 8 - 0,9=7,1 (zł)
b) m= k - z
c) -z= m-k
z= k-m
4.F= m*a /:m
a= F/m
F=m*a /:A
m=F/m
jakby co to pisz
a= P/h
2.a) L= 10π ( cm)
b) d= 2*r
d= 2*0,2
d=0,4 (dm)
L= 0,4π (dm)
3.k - z=m
m= 8 - 0,9=7,1 (zł)
b) m= k - z
c) -z= m-k
z= k-m
4.F= m*a /:m
a= F/m
F=m*a /:A
m=F/m
jakby co to pisz